The Importance of Implementing Security Management in the Era of Digital Transformation - Achmad Fauzi; Ratilla Amanda Edwar; Teti Aliyanti; Ayu Nur Jannah Milawati Candra; Amelia Seli Febrianti; Iqbal Al Baihaqi; Aditya Aji Nugroho (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
Cyber security is an important aspect of the increasingly complex cyber threats. This research uses a qualitative approach, namely a method using a literature review. This study was conducted to examine how events implement security management in this developing era and how to maintain data security. Human Resource Security is also very important in facing various threats in the digital transformation era which include SQL Injection, Phishing Attack, Fake News, Denial of Service, Malware & Ransomware, and others. Hackers' motivations for launching malware and DDoS attacks are usually to gain access to sensitive data, disrupt business operations, or exploit systems for illicit purposes. The goal is to consume system resources and cause business system failure.